An empirical examination of the relationship between organization’s learning culture and performance measurement system in Malaysia - Ong, Tze San; Teh, Boon Heng (Centre of Promoting Research Excellence, 2014)
This paper attempts to explore the adoption of performance measurement systems within Malaysia manufacturing organizations, using a brief literature review, theoretical conception and an empirical study of Malaysia organizations. This paper discusses the relationships between organization’s learning culture (i.e. knowledge & innovation; Learning Orientation; Absorptive Capability; Employees Understanding & Learning) and the characteristic of performance measurement system (PMS) (i.e adoption of non-financial measures and frequency of reporting). The findings indicate that organization’s learning culture appears to be the important variable tested which was found to be statistically correlated with characteristics of PMS (design of PMS and use of PMS).